Pengaruh FDI Dan IPM Terhadap Pertumbuhan Ekonomi Serta Kemiskinan Indonesia Tahun 2021-2023 (Jurnal Ekonomi Pembangunan Widya Mandira, 2025)
Since the pandemic disappeared in 2022-2023, the number of poor people in Indonesia has also decreased. The reduction in poverty in Indonesia during this period was caused by many factors. Poverty is a very complex problem that requires more efforts to overcome the problem. One of the efforts to overcome the problem of poverty is by investing in productive leading sectors in the form of Foreign Direct Investment (FDI). Therefore, good human resources are needed to absorb knowledge and technology due to the transfer of technology and knowledge from FDI itself which will ultimately encourage economic growth. Therefore, the main objective in this study is to examine the effect of FDI, HDI and economic growth on poverty. In this study, the data used is panel data consisting of 34 provinces in Indonesia for the period 2021-2023 with a total of 102 observations. Data were only taken from 34 provinces because four provinces did not have complete data due to the division of new provinces. The analysis model used in this research is Structural Equation Modeling (SEM). The results of the analysis show that FDI and HDI have an influence on increasing economic growth as seen from GRDP per capita. Further analysis shows that GRDP per capita has an influence on poverty reduction in Indonesia. This finding indicates that it is important to increase foreign investment and the quality of human resources in order to boost economic growth and ultimately reduce poverty. The implications for stakeholders of this study are that it is important for the government to create a conducive investment climate and improve the quality of human resources in order to achieve the goal of poverty reduction.